(untitled) (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Hepatitis C virus (HCV) infection is common in the patients undergoing hemodialysis (HD). The quality of life and survival of patients with hepatitis C infected end-stage renal disease is less than that of the noninfected ones. This study aims to determine the prevalence of HCV in patients undergoing HD and the risk of transmission. Methods: This was a retrospective study of charts of the chronic kidney disease patients who underwent dialysis at Patan Hospital from March 2011 to July 2017. Those patients who were positive for HIV, HBsAg and HCV before the initiation of dialysis were excluded. Pearson Chi square test and Fisher’s Exact test were used to determine the significance of the results. Results: Out of 173 patients, 12 (6.9%) seroconverted to HCV: five (41.66%) in first year, four (33.33%) in second year, and three (25%) in third year (Fisher’s Exact test p=0.26). Out of 173 patients, 137 (79.2%) received blood transfusion, 27 (15.6%) received erythropoiesis stimulating agent (ESA), 9 (5.2%) received both blood transfusion and ESA. The HCV seropositivity were 9 (75%), 2 (16.66%), and 1 (8.33%) respectively in them, Fisher’s Exact test p value was 0.65. There was no significant association between the seroconversions in in-center versus multicenter HD and the number of dialyses per week. Conclusions: Hepatitis C infection was common (6.9%) in HD patients. There was no significant association of transmission in regards to duration of HD, transfusion or single vs multicentre HD.